Assessing the Biophysical Impact and Financial Viability of Soil Management Technologies Under Variable Climate in Cabo Verde Drylands: The PESERA‐DESMICE Approach. (27th June 2016) - Baptista, Isaurinda; Irvine, Brian; Fleskens, Luuk; Geissen, Violette; Ritsema, Coen
Abstract: Field trials have demonstrated the potential of soil conservation technologies but have also shown significant spatial–temporal yield variability. This study considers the Pan‐European Soil Erosion Risk Assessment – Desertification Mitigation Cost‐Effectiveness modelling approach to capture a greater range of climatic conditions to assess the potential effect of an improved agricultural management practice emerged from field trials as a promising strategy for enhancing food security and reducing soil and land degradation. The model considers the biophysical and socio‐economic benefits of the improved soil conservation technique (T3) – residue mulch combined with pigeon pea hedges and an organic amendment, against a local baseline practice (T0). The historic rainfall statistics and 50‐year rainfall realizations provide a unique time series of rainfall and an envelope of the potential crop yield. Envelopes of potential biomass production help express the agricultural risk associated with climate variability and the potential of the conservation measures to absorb the risk, highlighting the uncertainty of a given crop yield being achieved in any particular year. T3 elevates yield under both sub‐humid and semi‐arid climates with greater security for sub‐humid areas even though risk of crop failure still exists. The technology offered good potential to increase yields by 20% in 42% of the dryland area in Santiago Island and reduce erosion by 8·6 Mg ha −1, but in terms of cost‐effectiveness, it might be prohibitively expensive for farmers lacking inputs. The findings can enable the assessment of policy options at larger scale or influence adoption of improved conservation measures under the climatic variability of the Cabo Verde drylands and resilience to future climate change. Copyright © 2016 John Wiley & Sons, Ltd.